Bio‐based epoxy‐anhydride thermosets from multi‐armed cardanol‐derived epoxy oligomers. (12th May 2022) - Liu, Xia; Fan, Weifeng; Yang, Xiaoniu
Abstract: Three bio‐based multi‐armed epoxy oligomers were synthesized via a ring‐opening reaction of cardanyl glycidyl ether with lignin‐derived polyphenols, followed by the epoxidation of the double bonds in the side chains of the cardanol segments. These oligomers were then used to prepare epoxy‐anhydride thermosets with 4‐methyl hexahydrophthalic anhydride (MHHPA) and 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene as the hardener and catalyst, respectively. The combination of differential scanning calorimetry and gel content results showed that the extent of cure was >90% when the formulations were heated at 110°C for 48 h. The cardanol‐derived thermosets exhibited markedly higher alpha transition temperatures ( T α ), tensile strength, and modulus relative to thermosets based on epoxidized soybean oil. The improved thermal and mechanical properties of these thermosets were attributed to the increased chain rigidity imparted by the aromatic moieties in the cardanol and creosol residues, as well as the hydrogen bonding interactions between the hydroxyl groups. Furthermore, the T α values of these thermosets increased with the anhydride equivalents and the functionality of the epoxides, which led to higher crosslinking densities and more rigid MHHPA contents.